A low volatile rubber-plastic product material and its preparation method and application

CN122917477APending Publication Date: 2026-10-16WINCELL INSULATION CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611294629.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有环保橡塑体系通常通过提高热塑性弹性体或聚烯烃连续相比例来增强力学性能,但有机相比例提高后易增加可燃组分占比,使无卤阻燃组分需要更高添加量才能发挥作用;而大量氢氧化镁、氢氧化铝或磷氮阻燃组分加入后,又可能造成填料团聚、界面缺陷和熔体流动性下降

Benefits of technology

1.本发明通过热塑性弹性体、聚烯烃树脂、天然橡胶和马来酸酐接枝聚丙烯构建相容连续相,使弹性链段和聚烯烃相之间形成较稳定的加工分散状态,从而在保持橡塑柔韧性的同时改善拉伸强度和成型稳定性,减少现有复配体系中相分离导致的力学波动。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917477A_ABST
    Figure CN122917477A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of environmental protection polymer materials, and provides a low-volatile rubber-plastic product material, a preparation method and application thereof. The present application matches and melt-blends the proportions of a thermoplastic elastomer, a polyolefin resin containing maleic anhydride grafted polypropylene, natural rubber, inorganic fillers containing surface-modified calcium carbonate, non-phthalate plasticizers, halogen-free flame-retardant components with a content greater than 0 in the formula, stable components and lubricating processing components, to form a rubber-plastic system with elastic continuous phase, interface compatibility and low-volatile control, to realize the synergistic improvement of mechanical strength, elongation at break, processing flow and low-volatile release, and to improve the oxygen index of the material in the implementation mode containing halogen-free flame-retardant components, to solve the problem that strength and flame retardance, flow and low migration are difficult to be considered in environmental protection rubber-plastic materials, and to be suitable for daily necessities, home cushion materials, automobile interiors, sports cushion materials, sealing strips, shoe materials and wire and cable sheaths and other products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmentally friendly polymer composite materials, specifically to a low-volatile rubber and plastic product material, its preparation method, and its application. Background Technology

[0002] Rubber and plastic products are widely used in daily necessities, children's products, household goods, sporting goods, footwear, automotive interior parts, wire and cable sheathing, and sealing products. Their material systems typically need to simultaneously meet requirements such as flexible touch, bending resistance, abrasion resistance, dimensional stability, processability, and safe contact. With the increasing trend towards low-odor, low-volatility, halogen-free, lead-free, and phthalic-free plasticizers, related products must not only maintain stable flow during extrusion, injection molding, calendering, or compression molding, but also reduce the release and migration of small molecules during long-term use. For floor mats, sports mats, low-odor automotive interior mats, and child contact products, the mechanical strength, elongation at break, flame retardancy, and environmental friendliness of the materials directly affect service life, contact safety, and product applicability. Therefore, constructing rubber and plastic material systems that balance processability, mechanical properties, flame retardancy, and low-release properties is of significant industrial importance.

[0003] Existing environmentally friendly rubber and plastic systems typically enhance mechanical properties by increasing the proportion of thermoplastic elastomers or polyolefins in the continuous phase. However, increasing the proportion of organic phase tends to increase the percentage of flammable components, requiring higher addition amounts of halogen-free flame-retardant components to be effective. Furthermore, the addition of large amounts of magnesium hydroxide, aluminum hydroxide, or phosphorus-nitrogen flame-retardant components can lead to filler agglomeration, interface defects, and decreased melt flowability. On the other hand, plasticizers are often introduced to reduce processing torque and improve molding flowability, but traditional plasticizer systems carry the risk of volatilization or migration. Simply reducing the amount of plasticizer can result in increased material hardness, decreased elasticity, and a narrowed processing window. For example, Chinese patent CN105907019A discloses halogen-free flame-retardant thermoplastic elastomer materials and their preparation methods. Its background section also mentions that existing halogen-free flame-retardant wire and cable materials still have limitations in terms of high-temperature resistance, dispersion, and mechanical properties, indicating that such systems still require further balancing between flame retardancy, mechanical properties, and processing capabilities. Summary of the Invention

[0004] The purpose of this invention is to provide a low-volatile rubber and plastic product material, its preparation method and application, to solve the problem that it is difficult to simultaneously achieve mechanical strength and flame retardancy, processing fluidity and low migration properties in current environmentally friendly rubber and plastic systems.

[0005] This invention constructs an elastic continuous phase using a thermoplastic elastomer and a polyolefin resin containing maleic anhydride-grafted polypropylene. The proportions of maleic anhydride-grafted polypropylene, surface-modified calcium carbonate, non-phthalate plasticizers, halogen-free flame retardant components with a content greater than 0 in the formulation, and stabilizing components are matched to weaken the mutual constraints between reinforcement, flame retardancy, flowability, and low release, thereby achieving performance characteristics that were originally difficult to satisfy simultaneously.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A low-volatile rubber and plastic product material, based on a total mass of 100 wt% of the formulation of the low-volatile rubber and plastic product material, is composed of the following formulation components, and the sum of the contents of each formulation component is 100 wt%: Thermoplastic elastomers 30.00-65.00 wt%; The polyolefin resin comprises 10.00-35.00 wt%, wherein the polyolefin resin includes one or two of polypropylene or polyethylene and maleic anhydride-grafted polypropylene, wherein the content of maleic anhydride-grafted polypropylene is 0.50-8.00 wt% and is included in the content of the polyolefin resin. Natural rubber 0.00-25.00wt%; The inorganic filler comprises 5.00-35.00 wt%, wherein the inorganic filler includes surface-modified calcium carbonate, and the content of the surface-modified calcium carbonate is 5.00-30.00 wt% and is included in the content of the inorganic filler; Non-phthalate plasticizers 5.00-30.00 wt%; Halogen-free flame retardant component 0.00-25.00wt%; Stable components: 0.10-3.00 wt%; Lubricating processing components: 0.10-3.00 wt%; Phthalate plasticizers, halogenated flame retardants, and lead salt stabilizers are not added as ingredients in the formulation of the low-volatile rubber and plastic products.

[0007] Furthermore, the corresponding components in the formulation each satisfy the following limitations: The thermoplastic elastomer is selected from one or both of styrene-ethylene / butene-styrene block copolymers or styrene-ethylene / propylene-styrene block copolymers. The matrix polyolefin resin in the polyolefin resin is selected from one or both of polypropylene and polyethylene. The inorganic filler is surface-modified calcium carbonate, or is composed of surface-modified calcium carbonate and talc. The non-phthalate plasticizer is selected from one or two of acetylated tributyl citrate and epoxidized soybean oil; The halogen-free flame retardant component with a content greater than 0 is selected from one or more of magnesium hydroxide, aluminum hydroxide, ammonium polyphosphate, or melamine cyanurate; The stabilizing component comprises calcium stearate, zinc stearate, and one or two selected from pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite; The lubricating component is selected from one or more of stearic acid, polyethylene wax, or erucamide.

[0008] Furthermore, the thermoplastic elastomer is a styrene-ethylene / butene-styrene block copolymer, and the quality control parameters of the styrene-ethylene / butene-styrene block copolymer are: styrene content of 15.00-35.00 wt%, number average molecular weight of 50,000-250,000 g / mol, and butadiene segment hydrogenation degree of 95.00-99.90%. The styrene content and the butadiene segment hydrogenation degree are determined by proton nuclear magnetic resonance spectroscopy using deuterated chloroform as solvent, and the number average molecular weight is determined by gel permeation chromatography using tetrahydrofuran as mobile phase and polystyrene as calibration standard.

[0009] Furthermore, the polyolefin resin includes maleic anhydride-grafted polypropylene as a compatibility modifying component. The content of the maleic anhydride-grafted polypropylene is 0.50-8.00 wt%, which is included in the content of the polyolefin resin. The quality control parameters of the maleic anhydride-grafted polypropylene are: maleic anhydride grafting rate of 0.30-2.00 wt%, and residual maleic anhydride content not exceeding 0.50 wt%. The maleic anhydride grafting rate is determined by acid-base titration, and the residual maleic anhydride content is determined by solvent extraction followed by acid-base titration.

[0010] Furthermore, the inorganic filler is surface-modified calcium carbonate, the content of which is 5.00-30.00 wt%, and is included in the content of the inorganic filler. The quality control parameters of the surface-modified calcium carbonate are: stearic acid surface treatment amount of 0.30-2.50 wt%, D50 particle size of 0.50-10.00 μm, and water content not higher than 0.50 wt%. The stearic acid surface treatment amount is recorded as the mass fraction of stearic acid relative to the mass of calcium carbonate raw material. The D50 particle size is determined by laser particle size distribution method, and the water content is determined by thermal weight loss method.

[0011] Furthermore, the non-phthalate plasticizer includes epoxidized soybean oil, and the content of the epoxidized soybean oil is included in the content of the non-phthalate plasticizer. The quality control parameters of the epoxidized soybean oil are: epoxy value of 5.50-7.50%, acid value not higher than 1.00 mg KOH / g, and volatile matter not higher than 0.50 wt%. The epoxy value is determined by the hydrochloric acid-acetone method or the hydrobromic acid-glacial acetic acid method, the acid value is determined by the potassium hydroxide titration method, and the volatile matter is determined by the heat loss method.

[0012] Furthermore, the halogen-free flame retardant component and the stabilizing component satisfy the following conditions: The content of the halogen-free flame retardant component is greater than 0, and the halogen-free flame retardant component is composed of magnesium hydroxide and ammonium polyphosphate, and the mass ratio of magnesium hydroxide to ammonium polyphosphate is 1:0.20-2.00. The stabilizing component consists of calcium stearate, zinc stearate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite, in a mass ratio of 1:0.20-2.00:0.05-1.00:0.05-1.00.

[0013] Furthermore, the low-volatile rubber and plastic product material, as measured by the methods described in the characterization and performance testing section of this specification, has a Shore A hardness of 45-95, a tensile strength of 5.00-25.00 MPa, an elongation at break of 150-800%, and a total volatile organic compound release of 0.05-3.00 mg / m³.

[0014] As a concept of this invention, it employs a compound design of thermoplastic elastomer, polyolefin resin, non-phthalate plasticizer, halogen-free flame-retardant component with a content greater than 0 in the formulation, surface-modified inorganic filler, stabilizing component, and lubricating processing component. This design primarily aims to achieve a synergistic balance between mechanical strength and flame-retardant properties. Existing systems, while reinforcing the continuous phase of thermoplastic elastomer and polyolefin typically improves strength and elasticity, increase the combustible organic phase and reduce the effective contribution of the halogen-free flame-retardant component. Adding flame-retardant components such as magnesium hydroxide or ammonium polyphosphate can easily disrupt the matrix continuity and reduce tensile strength and elongation at break. This invention improves compatibility and bonding through maleic anhydride grafted polypropylene, regulates filler dispersion through surface-modified calcium carbonate, and controls flow and release through non-phthalate plasticizer and stabilizing component. This allows the reinforcing phase, flame-retardant phase, and plasticizing phase to mutually correct each other within the same system, resulting in a material system that balances safe use and molding processing.

[0015] This invention also discloses a method for preparing low-volatile rubber and plastic materials, comprising the following steps: S1. Weigh the formulation components according to the above-mentioned low-volatile rubber and plastic product material formulation composition and formulation dosage, and premix the thermoplastic elastomer, the polyolefin resin, the natural rubber with a content greater than 0 in the formulation, the non-phthalate plasticizer, the stabilizing component and the lubricating processing component to obtain the first premix; S2. Add the inorganic filler and the halogen-free flame retardant component with a content greater than 0 in the formulation to the first premix, and continue mixing to obtain the second premix; S3. The second premix is ​​added to a twin-screw extruder for melt blending. The barrel temperature zone of the twin-screw extruder is set to 130-210℃, the screw speed is 100-600rpm, and the material residence time is 1.0-8.0min. S4. Extrude, cool, and pelletize the molten blend to obtain low-volatile rubber and plastic product granules; S5. The low-volatile rubber and plastic product material granules are extruded, injection molded, calendered or compression molded to obtain low-volatile rubber and plastic products.

[0016] Furthermore, in step S1, the premixing temperature is 20-60℃ and the premixing time is 3.0-20.0 min; in step S2, after the inorganic filler is added, the mixing temperature is 40-100℃ and the mixing time is 5.0-30.0 min.

[0017] Furthermore, in step S3, the twin-screw extruder is provided with multiple temperature zones along the material conveying direction, and the temperatures of the multiple temperature zones are 130-160℃, 150-180℃, 160-195℃ and 170-210℃ respectively; vacuum degassing is performed during the melt blending process, and the absolute pressure of the vacuum degassing section is 0.001-0.020MPa.

[0018] Further, in step S4, the cooling is water cooling or air cooling, and the moisture content of the low-volatile rubber and plastic product material granules after cooling is 0.02-0.50 wt%; in step S5, the low-volatile rubber and plastic product material granules are dried at 60-90℃ for 1.0-6.0h before molding, and the extrusion molding temperature is 140-210℃, the injection molding temperature is 150-220℃, and the compression molding temperature is 130-190℃.

[0019] This invention also discloses the application of a low-volatile rubber and plastic material, which is used to prepare daily necessities, household goods, sporting goods, wire and cable sheaths, sealing strips, floor mats, yoga mats, shoe materials, automotive interior parts, home floor mats, sports mats, or low-odor automotive interior mats; when the low-volatile rubber and plastic material contains the halogen-free flame-retardant component, it is used to prepare wire and cable sheaths; when the low-volatile rubber and plastic material does not contain the halogen-free flame-retardant component, it is used to prepare low-odor elastic cushioning sheets.

[0020] Furthermore, the styrene-ethylene / butene-styrene block copolymer is obtained through sequential anionic block polymerization of styrene and 1,3-butadiene followed by selective hydrogenation. Based on a total monomer mass of 100 parts by mass, styrene comprises 15-35 parts by mass, 1,3-butadiene comprises 65-85 parts by mass, cyclohexane is used as the polymerization solvent, the total monomer mass fraction is 10-35 wt%, and n-butyllithium is used as the initiator. The molar amount of n-butyllithium is calculated by dividing the total monomer mass by the target number-average molecular weight of 50,000-250,000 g / mol. The water content of the polymerization system is determined by the Karl Fischer method and controlled to be no higher than 200 ppm. The polymerization is carried out under nitrogen protection at 40-80℃ for 2.0-8.0 h to obtain a styrene-butadiene-styrene block copolymer solution.

[0021] Furthermore, when selectively hydrogenating the styrene-butadiene-styrene block copolymer solution, the styrene-butadiene-styrene block copolymer solution is transferred to a closed pressurized reactor, and a catalyst is added. The catalyst is selected from palladium-on-carbon catalyst, nickel-based catalyst, or cobalt-based catalyst. The amount of catalyst is 0.05-5.00 wt% of the mass of the styrene-butadiene-styrene block copolymer. The reaction is carried out at 60-120°C and hydrogen pressure of 1.0-6.0 MPa for 2.0-10.0 h. After the reaction, the catalyst is separated by filtration or centrifugation, and the styrene-ethylene / butene-styrene block copolymer is obtained by desolventizing and drying.

[0022] Furthermore, when the styrene-ethylene / butene-styrene block copolymer is a commercially purchased product, the purchased batch samples are subjected to hydrogen nuclear magnetic resonance spectroscopy and gel permeation chromatography. Hydrogen nuclear magnetic resonance spectroscopy uses deuterated chloroform as the solvent to record the integrals of aromatic hydrogen peaks, butadiene residual double bond peaks, and aliphatic hydrogen peaks, which are used to calculate the styrene content and the degree of hydrogenation of the butadiene segment. Gel permeation chromatography uses tetrahydrofuran as the mobile phase and polystyrene as the calibration standard to record the number-average molecular weight and molecular weight distribution, and the detection results are used as the quality control data for this batch entering the formulation.

[0023] Furthermore, the maleic anhydride-grafted polypropylene is prepared by a melt grafting reaction of polypropylene, maleic anhydride, and dicumyl peroxide. 100 parts by weight of polypropylene, 0.50-5.00 parts by weight of maleic anhydride, and 0.05-0.50 parts by weight of dicumyl peroxide are mixed and added to a twin-screw extruder. The melt grafting reaction is carried out at 170-210°C, a residence time of 1.0-5.0 min, and a screw speed of 100-500 rpm. A vacuum devolatilization section is set at the end of the twin-screw extruder, with an absolute pressure of 0.001-0.020 MPa. After extrusion, cooling, pelletizing, and drying at 60-90°C for 1.0-6.0 h, maleic anhydride-grafted polypropylene granules are obtained.

[0024] Furthermore, when testing the grafting rate and residual maleic anhydride content of the maleic anhydride-grafted polypropylene granules, the maleic anhydride-grafted polypropylene granules are crushed and sampled. The volume of alkali solution consumed is recorded by acid-base titration and the maleic anhydride grafting rate is calculated. Free maleic anhydride is detected by solvent extraction followed by acid-base titration. The extraction solvent, extraction time, titrant concentration, blank sample consumption, and sample consumption are recorded. The test results are used as the quality control data for the maleic anhydride-grafted polypropylene to be fed into the formulation.

[0025] Furthermore, the surface-modified calcium carbonate is obtained by surface treatment of calcium carbonate with stearic acid. 100 parts by weight of calcium carbonate are added to a high-speed mixer and dried and mixed at 80-120℃ for 10-40 minutes. Then, 0.50-3.00 parts by weight of stearic acid are added, and the mixture is surface-treated at 90-130℃ for 10-60 minutes. After cooling and sieving, surface-modified calcium carbonate is obtained. The amount of stearic acid surface treatment is recorded as the mass fraction of stearic acid relative to the mass of calcium carbonate raw material. The D50 particle size is detected by laser particle size distribution, and the moisture content is detected by thermal loss on weighing. The amount of stearic acid surface treatment, D50 particle size, and moisture content are used as quality control data for the surface-modified calcium carbonate to be incorporated into the formulation.

[0026] Furthermore, the epoxidized soybean oil is prepared by the epoxidation reaction of soybean oil. The molar number of carbon-carbon double bonds in soybean oil is determined by iodine value conversion. Based on the molar number of carbon-carbon double bonds in soybean oil, the molar ratio of carbon-carbon double bonds to hydrogen peroxide is 1:1.50-3.00. The amount of formic acid used is 5-25 mol% of the molar number of carbon-carbon double bonds, and the hydrogen peroxide is a 30-50% (w / w) aqueous solution. Soybean oil and formic acid are mixed, and the aqueous solution of hydrogen peroxide is added dropwise at 40-70℃ while maintaining the system temperature at 40-70℃. After the addition is completed, the reaction is continued for 3.0-8.0 h. After the reaction, the mixture is allowed to stand and separate into layers. The aqueous phase is removed and washed with deionized water until the pH of the aqueous phase is 6.00-8.00. Then, the mixture is dehydrated under reduced pressure at 60-90℃ and 0.001-0.010 MPa for 1.0-4.0 h to obtain epoxidized soybean oil.

[0027] Furthermore, when performing quality control on the epoxidized soybean oil, the epoxy value is determined using the hydrochloric acid-acetone method or the hydrobromic acid-glacial acetic acid method, the acid value is determined using the potassium hydroxide titration method, and the volatile matter is determined using the heat loss method. The sample mass, titrant concentration, blank consumption, sample consumption, heating temperature, heating time, and weight loss are recorded, and the epoxy value, acid value, and volatile matter are used as the quality control data for the epoxidized soybean oil to be added to the formulation.

[0028] Furthermore, the performance testing of the low-volatile rubber and plastic product material uses samples that have been placed at 23±2℃ for 24 hours after molding as test samples; the Shore A hardness is tested using a type A Shore hardness tester at 23±2℃, and the hardness value is read 3 seconds after pressure is applied; the tensile strength and elongation at break are tested using dumbbell-shaped specimens at 23±2℃ and a tensile speed of 500 mm / min, and the maximum tensile force, fracture displacement, effective cross-sectional area of ​​the specimen and gauge length changes are recorded, and the tensile strength and elongation at break are calculated accordingly.

[0029] Furthermore, the total volatile organic compound (VOC) release was measured using a low-VOC rubber and plastic product material sample that had been molded and placed at 23±2℃ for 24 hours. The sample was placed in a 1m³ environmental chamber with a test temperature of 65±2℃, a relative humidity of 50±10%, and an air exchange rate of 1.0±0.1h. - ¹, with an equilibration time of 2.0 h, the outlet gas of the environmental chamber was collected using adsorption tubes, and the total volatile organic compound (TVOC) concentration was analyzed by gas chromatography. Sample size, sample mass, exposure area, chamber volume, sampling volume, background concentration in the environmental chamber, TVOC concentration, blank subtraction method, and number of repetitions were recorded, with release amount recorded in mg / m³. The TVOC release amount in different embodiments is influenced by the polymer matrix, plasticizer, filler, flame retardant components, and raw material volatiles, and is not attributed solely to changes in the content of a single component.

[0030] Furthermore, when the low-volatile rubber and plastic material is used for low-odor elastic buffer sheets, the content of halogen-free flame retardant components in the formulation is 0 wt%, the non-phthalate plasticizer is selected from one or two of acetylated tributyl citrate and epoxidized soybean oil, and the stabilizing components consist of calcium stearate, zinc stearate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite; when the plasticizer migration rate test is performed on the molded elastic buffer sheet sample, the sample contact conditions, sample contact area, contact medium, contact time, contact temperature, mass change before and after the test and sensory change are recorded, and the plasticizer migration rate test data are used as the quality control data of the sample for this purpose.

[0031] As another aspect of this invention, the present invention employs a stepwise premixing, segmented feeding, twin-screw melt blending, and subsequent molding process, primarily to achieve, fix, or amplify the aforementioned synergistic effects. If all components are mixed at once, the low-viscosity plasticizer, powder filler, and halogen-free flame-retardant components with a content greater than 0 in the formulation are prone to localized uneven wetting or agglomeration, making it difficult to translate improved processing fluidity into stable mechanical and flame-retardant properties. Furthermore, increasing the melt shear strength alone may cause thermal shear damage to the elastomer chains and increased volatility of small molecules. This invention first forms a uniform first premix of thermoplastic elastomer, polyolefin resin, natural rubber, non-phthalate plasticizer, stabilizing components, and lubricating processing components. Then, inorganic fillers and halogen-free flame-retardant components with a content greater than 0 in the formulation are added. Dispersion and devolatilization are controlled by processing temperature, screw speed, residence time, and vacuum degassing, ensuring stable interfacial compatibility, filler distribution, flame-retardant component dispersion, and low-release control during processing. This invention also enables the aforementioned material systems to maintain their mechanical, flame-retardant, processable, and low-migration advantages in different usage environments by applying them to daily necessities, household goods, sporting goods, wire and cable sheaths, automotive interior parts, and low-odor elastic cushioning sheets.

[0032] Maleic anhydride-grafted polypropylene and surface-modified calcium carbonate primarily work synergistically around interfacial compatibility and filler dispersion. Maleic anhydride-grafted polypropylene is beneficial for improving the compatibility between polyolefin resins and polar fillers, but excessively high content may increase melt viscosity and affect elastic chain segment movement. Surface-modified calcium carbonate is beneficial for improving dimensional stability and filling reinforcement, but imbalances in particle size or treatment volume can easily lead to agglomeration and reduce elongation at break. This invention achieves mutual correction between interfacial bonding and dispersion by matching the maleic anhydride grafting rate, residual maleic anhydride content, stearic acid surface treatment amount, D50 particle size, and formulation ratio. When the halogen-free flame retardant component consists of magnesium hydroxide and ammonium polyphosphate, magnesium hydroxide and ammonium polyphosphate primarily work synergistically around flame retardancy and mechanical properties. Magnesium hydroxide tends to be more endothermic and dilutive, while ammonium polyphosphate tends to be more condensed and charred. Imbalances in the ratio of either component may result in filler burden or insufficient charring. This invention addresses these inherently contradictory properties through ratio matching.

[0033] Beneficial technical effects 1. This invention constructs a compatible continuous phase using thermoplastic elastomer, polyolefin resin, natural rubber, and maleic anhydride-grafted polypropylene, thereby creating a relatively stable processing dispersion state between the elastic segments and the polyolefin phase. This improves tensile strength and molding stability while maintaining the flexibility of rubber and plastic, and reduces mechanical fluctuations caused by phase separation in existing compound systems.

[0034] 2. In embodiments containing the halogen-free flame retardant component, the present invention uses magnesium hydroxide, ammonium polyphosphate and stabilizing components in combination. It utilizes the endothermic dilution and condensed phase protection effects of the halogen-free flame retardant component, and reduces the impact of processing heat and oxygen by the stabilizing component, so that the material can achieve a balance between flame retardancy and mechanical retention without adding halogenated flame retardants and lead salt stabilizers.

[0035] 3. This invention introduces non-phthalate plasticizers and combines them with epoxidized soybean oil quality control, vacuum degassing, and pre-molding drying to give the system better flow regulation capabilities during processing, while reducing the volatility and migration tendency of small molecules and improving the release risk of traditional plasticizer systems in low-odor products.

[0036] 4. This invention improves the dispersion and interfacial wetting of inorganic fillers in elastomer and polyolefin composite systems by controlling the amount of stearic acid treatment, D50 particle size and moisture content of surface-modified calcium carbonate, reducing the adverse effects of powder agglomeration on elongation at break and surface quality, and making it easier for products such as floor mats, shoe materials, sealing strips and automotive interior parts to obtain a uniform appearance and stable feel.

[0037] 5. The preparation method of the present invention adopts a combination of premixing, secondary feeding, twin-screw melt blending, vacuum degassing, cooling pelletizing and multiple molding methods, which can be adapted to extrusion, injection molding, calendering or compression molding, and facilitates formula adjustment in different scenarios such as wire and cable sheathing, low-odor elastic buffer sheets. Attached Figure Description

[0038] Figure 1 The figure shows the effect of maleic anhydride-grafted polypropylene content on tensile strength and melt flow rate of the rubber-plastic composite material in this scheme.

[0039] Figure 2 This diagram illustrates the effect of the particle size of surface-modified calcium carbonate D50 on tensile strength and elongation at break of the rubber-plastic composite material in this scheme.

[0040] Figure 3 This figure shows the effect of twin-screw extrusion processing temperature on tensile strength and melt mass flow rate of the rubber-plastic composite material in this scheme.

[0041] Figure 4 This figure shows the effect of the content of non-phthalate plasticizers on tensile strength and melt flow rate of the rubber-plastic composite material in this scheme.

[0042] Figure 5 This is a curve showing the difference in filler agglomeration size in the rubber-plastic composite material of this scheme.

[0043] Figure 6 This is a cumulative distribution curve of filler agglomeration size in the rubber-plastic composite material of this scheme.

[0044] Figure 7 This is a graph showing the relationship between melt flow rate and tensile strength of the rubber-plastic composite material in this scheme.

[0045] Figure 8 This is a comparative chart showing the oxygen index and tensile strength of the rubber-plastic composite material in this scheme.

[0046] Figure 9 This is a thermogravimetric analysis mass retention curve of the rubber-plastic composite material in this scheme.

[0047] Figure 10 This is a comparison chart of the total volatile organic compound release and plasticizer migration rate of the rubber-plastic composite material in this scheme.

[0048] Figure 11 This is a scatter plot of the epoxy value quality control for epoxidized soybean oil in this scheme.

[0049] Figure 12 This is a scatter plot of the acid value quality control for epoxidized soybean oil in this scheme.

[0050] Figure 13 This is a scatter plot of the volatile matter content of epoxidized soybean oil in this scheme.

[0051] Figure 14 The images show a macroscopic optical photograph comparison between the low-volatile rubber and plastic product material granules and extruded sheets of Example 1 and the final product of Comparative Example 2; where a is a macroscopic optical photograph of the final product of Example 1, the sample including low-volatile rubber and plastic product material granules and extruded sheets; and b is a macroscopic optical photograph of the final product of Comparative Example 2.

[0052] Figure 15 The images show a comparison of the scanning electron microscope (SEM) morphology of the low-volatile rubber and plastic product granules and extruded sheets of Example 1 with the final product of Comparative Example 2. Specifically, a is a low-magnification SEM image of the final product of Example 1; b is a low-magnification SEM image of the final product of Comparative Example 2; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 2; e is a high-magnification SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 2.

[0053] Figure 16 The images show a comparison of the transmission electron microscope (TEM) structures of the low-volatile rubber and plastic product granules and extruded sheets of Example 1 and the final product of Comparative Example 2; where a is a bright-field TEM image of the final product of Example 1; b is a bright-field TEM image of the final product of Comparative Example 2; c is a high-resolution TEM image of the final product of Example 1; d is a high-resolution TEM image of the final product of Comparative Example 2; e is an elemental distribution map of the final product of Example 1; and f is an elemental distribution map of the final product of Comparative Example 2. Detailed Implementation

[0054] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0055] Example 1 A low-volatile rubber and plastic product material granules and extruded sheets are prepared in the following manner, with a preparation scale of 1000.00g. The product form is granules and extruded sheets that can be used for home floor mats, sports mats and flame-retardant elastic mat materials.

[0056] Raw materials and proportions: Based on a total mass of 100 wt% for the formulation, the thermoplastic elastomer in this embodiment is 30.00 wt%, using a styrene-ethylene / butene-styrene block copolymer with a styrene content of 15.00 wt%, a number-average molecular weight of 50,000 g / mol, and a butadiene segment hydrogenation degree of 95.00%. This is a commercially available polymer material, and batch quality control data were confirmed by hydrogen nuclear magnetic resonance spectroscopy and gel permeation chromatography before feeding. The polyolefin resin in this embodiment is 10.00 wt%, composed of polypropylene 9... The composition consists of 0.50 wt% maleic anhydride-grafted polypropylene and 0.50 wt% maleic anhydride-grafted polypropylene, with a maleic anhydride grafting rate of 0.30 wt% and a residual maleic anhydride content of 0.50 wt%. The natural rubber in this embodiment is 11.80 wt%, using commercially available solid natural rubber with volatile matter ≤0.80 wt%. The inorganic filler in this embodiment is 35.00 wt%, composed of 30.00 wt% surface-modified calcium carbonate and 5.00 wt% talc. The surface-modified calcium carbonate is treated with stearic acid on its surface. The physical content is 2.50 wt%, the D50 particle size is 10.00 μm, and the water content is 0.50 wt%. The non-phthalate plasticizer in this embodiment is 5.00 wt%, made from epoxidized soybean oil with an epoxy value of 5.50%, an acid value of 1.00 mg KOH / g, and volatile matter of 0.50 wt%. The halogen-free flame retardant component in this embodiment is 5.00 wt%, composed of 4.17 wt% magnesium hydroxide and 0.83 wt% ammonium polyphosphate, with a mass ratio of magnesium hydroxide to ammonium polyphosphate of 1:0.20. The stabilizing component of this embodiment is 0.20 wt%, consisting of 0.1538 wt% calcium stearate, 0.0308 wt% zinc stearate, 0.0077 wt% pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.0077 wt% tris(2,4-di-tert-butylphenyl) phosphite. The lubricating component of this embodiment is 3.00 wt%, consisting of 1.00 wt% stearic acid, 1.50 wt% polyethylene wax, and 0.50 wt% erucamide. All the above components are commercially available or purchased raw materials, and no phthalate plasticizers, halogenated flame retardants, or lead salt stabilizers are used.

[0057] S1: Styrene-ethylene / butene-styrene block copolymer, polypropylene, maleic anhydride-grafted polypropylene, natural rubber, epoxidized soybean oil, calcium stearate, zinc stearate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl) phosphite, stearic acid, polyethylene wax and erucamide are sequentially added to a high-speed mixer and premixed at 300 rpm for 3.0 min at 20°C to obtain the first premix.

[0058] S2: Add surface-modified calcium carbonate, talc, magnesium hydroxide and ammonium polyphosphate to the first premix, and continue mixing at 500 rpm for 5.0 min at 40°C to obtain the second premix. The criterion for the end of mixing is that there are no visible agglomerates in the powder and the mass fraction of large particle aggregates is less than 0.10 wt% during sampling and screening.

[0059] S3: Add the second premix to a co-rotating twin-screw extruder for melt blending. The four temperature zones of the twin-screw extruder along the material conveying direction are set to 130℃, 150℃, 160℃ and 170℃ respectively. The main processing temperature is controlled at 130℃, the screw speed is 100rpm, the material residence time is 1.0min, the absolute pressure of the vacuum exhaust section is 0.020MPa, the melt pressure at the die head is kept within a stable fluctuation range, and the melt is judged to be completed when the melt is continuously discharged from the die orifice and no bubbles are observed.

[0060] S4: After the melt blend is extruded into strips, it is cooled by water cooling at a temperature of 25°C. After the strips are no longer sticky, they are cut into pellets to obtain low-volatile rubber and plastic product material pellets. The moisture content of the pellets is measured to be 0.50wt% after being treated with hot air at 60°C for 30 minutes.

[0061] S5: The low-volatile rubber and plastic material granules were dried at 60°C for 1.0 h, and then sheets were prepared at an extrusion molding temperature of 140°C. Mechanical samples were prepared at an injection molding temperature of 150°C and a compression molding temperature of 130°C, respectively. The surface of the obtained sheets was continuous, and no coke particles, bubbles or white powder were observed.

[0062] Main quality testing methods and results: After the molded sample was placed at 23±2℃ for 24h, the Shore A hardness was 72±2, the tensile strength was 9.80±0.40MPa, the elongation at break was 260±18%, the total volatile organic compound release was 2.40±0.20mg / m³, the oxygen index was 24.5±0.4%, and the number of test repetitions was n=3.

[0063] Features and application scenarios of this embodiment: This embodiment adopts an elastomer ratio biased towards the low-value region and a higher proportion of surface-modified inorganic fillers, combined with lower processing strength and higher lubrication processing components, which is suitable for preparing home floor mats, sports mats and flame-retardant elastic sheets with high requirements for dimensional stability, surface feel and extrusion molding continuity.

[0064] Example 2 In this embodiment, low-volatile rubber and plastic product granules were prepared with a feed rate of 1500.00g, and the resulting granules were processed into wire and cable sheath samples. All components used commercially available or purchased raw materials, and the powder moisture content, plasticizer volatiles, and residual maleic anhydride content of the compatibility modifier were controlled before feeding.

[0065] The raw material composition is as follows: 30.00 wt% thermoplastic elastomer, composed of 24.00 wt% styrene-ethylene / butene-styrene block copolymer and 6.00 wt% styrene-ethylene / propylene-styrene block copolymer, wherein the styrene content of the styrene-ethylene / butene-styrene block copolymer is 25.00 wt%, the number average molecular weight is 120000 g / mol, and the hydrogenation degree of the butadiene segment is 98.00%; 10.00 wt% polyolefin resin, composed of 2.00 wt% polypropylene and 8.00 wt% maleic anhydride-grafted polypropylene, the maleic anhydride grafting rate of the maleic anhydride-grafted polypropylene is 2.00 wt%, and the residual maleic anhydride content is 0.05 wt%; 24.80 wt% natural rubber; 5.00 wt% inorganic filler, which is surface-modified calcium carbonate, with a stearic acid surface treatment amount of 0.30 wt% and a D50 particle size of 0.50 μm. The water content is 0.10 wt%; the non-phthalate plasticizer is 5.00 wt%, composed of 2.50 wt% tributyl acetylacetonate and 2.50 wt% epoxidized soybean oil, with an epoxy value of 6.50%, an acid value of 0.50 mg KOH / g, and volatile matter of 0.20 wt%; the halogen-free flame retardant component is 25.00 wt%, composed of 8.33 wt% magnesium hydroxide and 16.67 wt% ammonium polyphosphate. The mass ratio of magnesium oxide to ammonium polyphosphate is 1:2.00; the stabilizing component is 0.10 wt%, consisting of 0.0769 wt% calcium stearate, 0.0154 wt% zinc stearate, 0.00385 wt% pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.00385 wt% tris(2,4-di-tert-butylphenyl) phosphite; the lubricating component is 0.10 wt%, which is stearic acid.

[0066] Preparation process: First, thermoplastic elastomer, polypropylene, maleic anhydride-grafted polypropylene, natural rubber, tributyl acetylacetic acid, epoxidized soybean oil, stabilizing components, and stearic acid are added to a high-speed mixer and premixed at 400 rpm for 20.0 min at 60°C to obtain the first premix. Subsequently, surface-modified calcium carbonate, magnesium hydroxide, and ammonium polyphosphate are added, and the mixture is mixed at 700 rpm for 30.0 min at 100°C to obtain the second premix. The powder addition process is completed in three batches, with a 2.0 min interval between each batch to ensure sufficient powder wetting and reduce local agglomeration.

[0067] Melt blending process: The second premix is ​​added to a twin-screw extruder. The four temperature zones along the material conveying direction are set sequentially to 160℃, 180℃, 195℃, and 210℃, with a main processing temperature of 210℃, a screw speed of 600 rpm, a material residence time of 8.0 min, and an absolute pressure of 0.001 MPa in the vacuum exhaust section. After passing through a filter screen, the melt is stably extruded from the die head. Cooling and pelletizing are performed when the surface of the melt strip is continuous and no unmelted particles are observed.

[0068] Post-processing and molding: The extruded strip was cooled by air cooling, and the moisture content of the pellets after pelleting was 0.02 wt%. The pellets were dried at 90℃ for 6.0 h, and then sheath strips, dumbbell-shaped samples, and sheet samples were prepared at extrusion molding temperature of 210℃, injection molding temperature of 220℃, and compression molding temperature of 190℃, respectively. The molded samples were placed at 23±2℃ for 24 h for quality evaluation.

[0069] Main quality testing methods and results: Shore A hardness is 90±2, tensile strength is 10.50±0.50MPa, elongation at break is 170±15%, total volatile organic compound release is 2.70±0.20mg / m³, oxygen index is 31.0±0.5%, and the number of test repetitions is n=3.

[0070] The features of this embodiment are: This embodiment uses a high proportion of natural rubber and a high proportion of halogen-free flame retardant components, and uses strong melt mixing and sufficient vacuum degassing conditions, which is suitable for preparing wire and cable sheaths, flame retardant foot pads and elastic products with high requirements for flame retardant safety.

[0071] Example 3 This embodiment employs a parameter-first, process-expanding approach. The preparation scale is 1200.00g, and the product form is high-hardness, low-odor rubber-plastic granules and injection-molded automotive interior mat samples.

[0072] The key proportions in this embodiment are as follows: 65.00 wt% thermoplastic elastomer, a styrene-ethylene / butene-styrene block copolymer with a styrene content of 35.00 wt%, a number-average molecular weight of 250,000 g / mol, and a butadiene segment hydrogenation degree of 99.90%; 10.00 wt% polyolefin resin, composed of 5.00 wt% polyethylene, 4.00 wt% polypropylene, and 1.00 wt% maleic anhydride-grafted polypropylene, with a maleic anhydride grafting rate of 1.20 wt% and a residual maleic anhydride content of 0.20 wt%; 0 wt% natural rubber; and 5.00 wt% inorganic filler, surface-modified calcium carbonate with a stearic acid surface treatment amount of 1.30 wt%, a D50 particle size of 2.00 μm, and a water content of [missing information]. 0.20wt%; 5.00wt% non-phthalate plasticizer, which is epoxidized soybean oil with an epoxy value of 6.20%, an acid value of 0.30 mg KOH / g, and 0.20wt% volatile matter; 11.80wt% halogen-free flame retardant, composed of 5.90wt% magnesium hydroxide and 5.90wt% ammonium polyphosphate, with a mass ratio of magnesium hydroxide to ammonium polyphosphate of 1:1.00; 3.00wt% stabilizing component, composed of 0.60wt% calcium stearate, 1.20wt% zinc stearate, 0.60wt% pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.60wt% tris(2,4-di-tert-butylphenyl) phosphite; 0.20wt% lubricating processing component, which is polyethylene wax. The total mass of all ingredients is 100wt%.

[0073] Premixing stage: Styrene-ethylene / butene-styrene block copolymer, polyethylene, polypropylene, maleic anhydride-grafted polypropylene, epoxidized soybean oil, stabilizing components, and polyethylene wax are added to a high-speed mixer and premixed for 10.0 min at 40°C and 350 rpm to form the first premix. No powder is added in this stage to reduce interference from powder on the initial wetting of the elastomer and polyolefin resin.

[0074] Filler and flame retardant component dispersion stage: Surface-modified calcium carbonate, magnesium hydroxide, and ammonium polyphosphate were added to the first premix, and the mixing temperature was raised to 70℃. The mixture was then mixed at 650 rpm for 15.0 min to obtain the second premix. After mixing, samples were taken from three different locations for screening. When the mass fraction of large particle aggregates in the samples was less than 0.10 wt%, the mixture was allowed to proceed to the extrusion stage.

[0075] Melt blending stage: The second premix is ​​added to a twin-screw extruder. The four temperature zones are set to 145℃, 165℃, 180℃, and 190℃ respectively, the main processing temperature is 170℃, the screw speed is 300 rpm, the material residence time is 4.0 min, and the absolute pressure of the vacuum exhaust section is 0.010 MPa. During extrusion, the main extruder current is kept stable. After the melt is continuously discharged without pulsation, traction and cooling are performed.

[0076] Cooling, pelletizing, and molding stage: The melt strip was water-cooled at 25°C and then pelletized, with a pellet moisture content of 0.20 wt%. After drying the pellets at 80°C for 3.0 h, automotive interior mat samples were prepared at an injection molding temperature of 190°C, sheets were prepared at an extrusion molding temperature of 180°C, and mechanical testing samples were prepared at a compression molding temperature of 160°C.

[0077] Main quality testing methods and results: The molded sample was tested after being placed at 23±2℃ for 24 hours. The Shore A hardness was 95±1, the tensile strength was 20.00±1.00MPa, the elongation at break was 480±25%, the total volatile organic compound release was 0.90±0.10mg / m³, the oxygen index was 28.5±0.4%, and the number of test repetitions was n=3.

[0078] The process features and application directions of this embodiment: This embodiment adopts a high thermoplastic elastomer content, a high stable component content and a medium flame retardant ratio to form a material system with high hardness, low odor and good mechanical retention, which is suitable for low-odor automotive interior mats, shoe support components and wear-resistant elastic products.

[0079] Example 4 The low-odor elastic buffer sheet was prepared as the target product. In this example, a feed scale of 1000.00g was used. The resulting low-volatile rubber and plastic product material granules were molded and injection molded into elastic buffer sheets, sheet-like strips and dumbbell-shaped specimens.

[0080] I. Preparation Object and Raw Material State: The thermoplastic elastomer in this embodiment is 30.00 wt%, made of styrene-ethylene / butene-styrene block copolymer, with a styrene content of 20.00 wt%, a number-average molecular weight of 200,000 g / mol, and a butadiene segment hydrogenation degree of 99.00%. The polyolefin resin in this embodiment is 34.90 wt%, composed of 24.90 wt% polypropylene, 6.00 wt% polyethylene, and 4.00 wt% maleic anhydride-grafted polypropylene. The maleic anhydride grafting rate of the maleic anhydride-grafted polypropylene is 1.00 wt%, and the residual maleic anhydride content is 0.10 wt%. The natural rubber in this embodiment is 0 wt%.

[0081] II. Formulation Components and Quality Control: The inorganic filler in this embodiment is 5.00 wt%, using surface-modified calcium carbonate, with a stearic acid surface treatment amount of 2.00 wt%, a D50 particle size of 5.00 μm, and a water content of 0.10 wt%. The non-phthalate plasticizer in this embodiment is 29.90 wt%, composed of 20.00 wt% tributyl acetylacetonate and 9.90 wt% epoxidized soybean oil. The epoxidized soybean oil has an epoxy value of 7.50%, an acid value of 0.10 mg KOH / g, and a volatile matter content of 0.10 wt%. The halogen-free flame retardant component in this embodiment is 0 wt%. The stabilizing component of this embodiment is 0.10 wt%, consisting of 0.0400 wt% calcium stearate, 0.0400 wt% zinc stearate, 0.0100 wt% pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.0100 wt% tris(2,4-di-tert-butylphenyl) phosphite. The lubricating component of this embodiment is 0.10 wt%, using erucamide. All the above components are commercially available or purchased raw materials, and no phthalate plasticizers, halogenated flame retardants, or lead salt stabilizers are added.

[0082] III. Mixing and Melt Blending: Thermoplastic elastomer, polypropylene, polyethylene, maleic anhydride-grafted polypropylene, tributyl acetylacetic acid, epoxidized soybean oil, stabilizing components, and erucamide were sequentially added to a mixing device and premixed at 300 rpm for 15.0 min at 25°C to obtain the first premix. Subsequently, surface-modified calcium carbonate was added, and the mixture was mixed at 500 rpm for 10.0 min at 45°C to obtain the second premix. The second premix was fed into a twin-screw extruder with four temperature zones set sequentially to 130°C, 150°C, 160°C, and 170°C. The main processing temperature was 150°C, the screw speed was 200 rpm, the material residence time was 3.0 min, and the absolute pressure in the vacuum exhaust section was 0.020 MPa.

[0083] IV. Cooling, Pelletizing, and Product Molding: After extrusion, the melt blend was cooled by air cooling, resulting in pellets with a moisture content of 0.10 wt%. The pellets were dried at 70℃ for 2.0 h, then used to prepare elastic buffer sheets at a compression molding temperature of 150℃, dumbbell-shaped samples at an injection molding temperature of 170℃, and sheets at an extrusion molding temperature of 140℃. After molding, the samples were placed at 23±2℃ for 24 h before performance and migration evaluation.

[0084] V. Main quality testing methods and results: Shore A hardness is 45±2, tensile strength is 6.50±0.30MPa, elongation at break is 780±35%, total volatile organic compound release is 0.08±0.02mg / m³, oxygen index is 20.2±0.3%, melt flow rate is 8.6±0.4g / 10min, plasticizer migration rate is 0.42±0.05%, and the number of test repetitions is n=3.

[0085] VI. Applicable Scenarios of this Embodiment: This embodiment uses high-polyolefin resin and high-non-phthalate plasticizer, without adding halogen-free flame retardant components, and is suitable for low-odor elastic cushioning sheets and auxiliary parts of daily necessities with high requirements for soft touch and low release.

[0086] Comparative Example 1: Basically the same as Example 1, except that 5.00 wt% of epoxidized soybean oil in the non-phthalate plasticizer was replaced with 5.00 wt% of phthalate plasticizer, and the position was changed to the raw material and proportioning stage; other conditions were kept the same as follows: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, halogen-free flame retardant component 5.00 wt%, stabilizing component 0.20 wt%, lubricating processing component 3.00 wt%, S1 premixing temperature 20℃, premixing time 3.0 min, S2 mixing temperature 40℃, mixing time 5.0 min, twin-screw extruder four temperature zones 130℃, 150℃, 160℃ and 170℃, screw speed 100 rpm, material residence time 1.0 min, absolute pressure of vacuum exhaust section 0.020 MPa, granule moisture content 0.50 wt%, drying at 60℃ for 1.0 h before molding.

[0087] Comparative Example 2: Essentially the same as Example 1, except that 30.00 wt% of surface-modified calcium carbonate was replaced with 30.00 wt% of unmodified calcium carbonate, and the addition of inorganic filler was changed to the inorganic filler addition stage. Other conditions remained the same: 30.00 wt% thermoplastic elastomer, 10.00 wt% polyolefin resin, 11.80 wt% natural rubber, 35.00 wt% inorganic filler, 5.00 wt% non-phthalate plasticizer, 5.00 wt% halogen-free flame retardant component, and stabilizer. The composition of the extruder is 0.20 wt% and the lubricating processing component is 3.00 wt%. The S1 premixing temperature is 20℃ and the premixing time is 3.0 min. The S2 mixing temperature is 40℃ and the mixing time is 5.0 min. The twin-screw extruder has four temperature zones: 130℃, 150℃, 160℃ and 170℃. The screw speed is 100 rpm and the material residence time is 1.0 min. The absolute pressure of the vacuum exhaust section is 0.020 MPa. The moisture content of the granules is 0.50 wt%. The material is dried at 60℃ for 1.0 h before molding.

[0088] Comparative Example 3: Essentially the same as Example 1, except that the D50 particle size of the surface-modified calcium carbonate was adjusted from 10.00 μm to 15.00 μm, and the location was changed to the inorganic filler quality control stage; other conditions remained the same: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, non-phthalate plasticizer 5.00 wt%, halogen-free flame retardant 5.00 wt%, stabilizing component 0.20 wt%, and lubricating component 3.00 wt%. The surface-modified calcium carbonate content is 30.00wt%, the stearic acid surface treatment amount is 2.50wt%, and the water content is 0.50wt%. The S1 premixing temperature is 20℃ and the premixing time is 3.0min. The S2 mixing temperature is 40℃ and the mixing time is 5.0min. The twin-screw extruder has four temperature zones of 130℃, 150℃, 160℃ and 170℃. The screw speed is 100rpm and the material residence time is 1.0min. The absolute pressure of the vacuum exhaust section is 0.020MPa. The granule water content is 0.50wt%. The material is dried at 60℃ for 1.0h before molding.

[0089] Comparative Example 4: Essentially the same as Example 1, except that maleic anhydride-grafted polypropylene was not added to the polyolefin resin, and the polypropylene content was adjusted to 10.00 wt%. The component was changed to the polyolefin resin composition stage. Other conditions remained the same: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, non-phthalate plasticizer 5.00 wt%, and halogen-free flame retardant 5.00 wt%. The composition includes: 0.20 wt% stabilizing component, 3.00 wt% lubricating component, S1 premixing temperature 20℃, premixing time 3.0 min, S2 mixing temperature 40℃, mixing time 5.0 min, twin-screw extruder with four temperature zones of 130℃, 150℃, 160℃ and 170℃, screw speed 100 rpm, material residence time 1.0 min, absolute pressure of vacuum exhaust section 0.020 MPa, pellet moisture content 0.50 wt%, and drying at 60℃ for 1.0 h before molding.

[0090] Comparative Example 5: Basically the same as Example 1, except that the main processing temperature of the twin-screw extruder was adjusted from 130℃ to 120℃, and the four temperature zones were set to 120℃, 140℃, 150℃ and 160℃ respectively. The location was changed to the melt blending stage. Other conditions were kept the same: thermoplastic elastomer 30.00wt%, polyolefin resin 10.00wt%, natural rubber 11.80wt%, inorganic filler 35.00wt%, non-phthalate plasticizer 5.00wt%, halogen-free flame retardant 5.00wt%, stabilizing component 0.20wt%, lubricating processing component 3.00wt%, S1 premixing temperature 20℃, premixing time 3.0min, S2 mixing temperature 40℃, mixing time 5.0min, screw speed 100rpm, material residence time 1.0min, absolute pressure of vacuum exhaust section 0.020MPa, granule moisture content 0.50wt%, and drying at 60℃ for 1.0h before molding.

[0091] Comparative Example 6: Basically the same as Example 1, except that the screw speed of the twin-screw extruder was adjusted from 100 rpm to 700 rpm, and the position was changed to the melt blending stage; other conditions were kept the same: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, non-phthalate plasticizer 5.00 wt%, halogen-free flame retardant 5.00 wt%, stabilizing component 0.20 wt%, lubricating processing component 3.00 wt%, S1 premixing temperature 20℃, premixing time 3.0 min, S2 mixing temperature 40℃, mixing time 5.0 min, four temperature zones of the twin-screw extruder 130℃, 150℃, 160℃ and 170℃, material residence time 1.0 min, absolute pressure of vacuum exhaust section 0.020 MPa, granule moisture content 0.50 wt%, drying at 60℃ for 1.0 h before molding.

[0092] Comparative Example 7: Basically the same as Example 1, except that the absolute pressure of the vacuum exhaust section was adjusted from 0.020 MPa to 0.050 MPa, and the location was changed to the melt blending exhaust stage; other conditions were kept the same as follows: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, non-phthalate plasticizer 5.00 wt%, halogen-free flame retardant component 5.00 wt%, stabilizing component 0.20 wt%, lubricating processing component 3.00 wt%, S1 premixing temperature 20℃, premixing time 3.0 min, S2 mixing temperature 40℃, mixing time 5.0 min, twin-screw extruder four temperature zones 130℃, 150℃, 160℃ and 170℃, screw speed 100 rpm, material residence time 1.0 min, pellet moisture content 0.50 wt%, drying at 60℃ for 1.0 h before molding.

[0093] Comparative Example 8: Essentially the same as Example 1, except that the stabilizing component consists solely of 0.20 wt% calcium stearate, without the addition of zinc stearate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and tris(2,4-di-tert-butylphenyl) phosphite; its position is changed to the stabilizing component composition stage. Other conditions remain the same: 30.00 wt% thermoplastic elastomer, 10.00 wt% polyolefin resin, 11.80 wt% natural rubber, 35.00 wt% inorganic filler, and non-phthalate esters. The mixture contains 5.00 wt% plasticizer, 5.00 wt% halogen-free flame retardant, and 3.00 wt% lubricating processing component. The S1 premixing temperature is 20℃ and the premixing time is 3.0 min. The S2 mixing temperature is 40℃ and the mixing time is 5.0 min. The twin-screw extruder has four temperature zones: 130℃, 150℃, 160℃ and 170℃. The screw speed is 100 rpm. The material residence time is 1.0 min. The absolute pressure of the vacuum exhaust section is 0.020 MPa. The moisture content of the pellets is 0.50 wt%. The pellets are dried at 60℃ for 1.0 h before molding.

[0094] Comparative Example 9: Essentially the same as Example 1, except that the halogen-free flame retardant component is composed solely of 5.00 wt% magnesium hydroxide, without the addition of ammonium polyphosphate, and its position is changed to the halogen-free flame retardant component composition stage; other conditions remain the same: 30.00 wt% thermoplastic elastomer, 10.00 wt% polyolefin resin, 11.80 wt% natural rubber, 35.00 wt% inorganic filler, 5.00 wt% non-phthalate plasticizer, 5.00 wt% total halogen-free flame retardant component, and stable... The sample consisted of a fixed component of 0.20 wt% and a lubricating processing component of 3.00 wt%. Premixing temperature (S1) was 20℃, and premixing time was 3.0 min. Mixing temperature (S2) was 40℃, and mixing time was 5.0 min. The twin-screw extruder was used with four temperature zones: 130℃, 150℃, 160℃, and 170℃. The screw speed was 100 rpm, the material residence time was 1.0 min, the absolute pressure in the vacuum exhaust section was 0.020 MPa, and the pellet moisture content was 0.50 wt%. The pellets were dried at 60℃ for 1.0 h before molding. This comparative example was used to investigate the synergistic relationship between magnesium hydroxide and ammonium polyphosphate.

[0095] Comparative Example 10: Essentially the same as Example 1, except that the halogen-free flame retardant component is composed solely of 5.00 wt% ammonium polyphosphate, without the addition of magnesium hydroxide, and its position is changed to the halogen-free flame retardant component composition stage; other conditions remain the same: 30.00 wt% thermoplastic elastomer, 10.00 wt% polyolefin resin, 11.80 wt% natural rubber, 35.00 wt% inorganic filler, 5.00 wt% non-phthalate plasticizer, 5.00 wt% total halogen-free flame retardant component, and stable... The sample consisted of a fixed component of 0.20 wt% and a lubricating processing component of 3.00 wt%. Premixing temperature (S1) was 20℃, and premixing time was 3.0 min. Mixing temperature (S2) was 40℃, and mixing time was 5.0 min. The twin-screw extruder was used with four temperature zones: 130℃, 150℃, 160℃, and 170℃. The screw speed was 100 rpm, the material residence time was 1.0 min, the absolute pressure in the vacuum exhaust section was 0.020 MPa, and the pellet moisture content was 0.50 wt%. The pellets were dried at 60℃ for 1.0 h before molding. This comparative example was used to investigate the synergistic relationship between magnesium hydroxide and ammonium polyphosphate.

[0096] Comparative Example 11: Essentially the same as Example 1, except that the halogen-free flame retardant component still consists of magnesium hydroxide and ammonium polyphosphate, but the mass ratio of magnesium hydroxide to ammonium polyphosphate is adjusted to 1:3.00, with magnesium hydroxide at 1.25 wt% and ammonium polyphosphate at 3.75 wt%. The position is changed to the halogen-free flame retardant component proportion stage; other conditions remain the same: thermoplastic elastomer 30.00 wt%, polyolefin resin 10.00 wt%, natural rubber 11.80 wt%, inorganic filler 35.00 wt%, and non-phthalate plasticizer 5.00 wt%. The composition of the halogen-free flame retardant component was 5.00 wt%, the stabilizing component was 0.20 wt%, and the lubricating component was 3.00 wt%. The premixing temperature for S1 was 20℃, and the premixing time was 3.0 min. The mixing temperature for S2 was 40℃, and the mixing time was 5.0 min. The twin-screw extruder had four temperature zones: 130℃, 150℃, 160℃, and 170℃. The screw speed was 100 rpm, the material residence time was 1.0 min, the absolute pressure in the vacuum exhaust section was 0.020 MPa, the granule moisture content was 0.50 wt%, and the material was dried at 60℃ for 1.0 h before molding. This comparative example was used to investigate the synergistic relationship between magnesium hydroxide and ammonium polyphosphate.

[0097] Characterization and performance testing: Using the molded sheets and dumbbell-shaped specimens from Examples 1–4 and all comparative examples as test objects, the Shore A hardness was evaluated to confirm the compatibility of the material's hardness with applications in daily necessities, padding materials, sheaths, and elastic cushioning sheets. The tests were conducted according to GB / T2411-2008 "Determination of Indentation Hardness (Shore Hardness) of Plastics and Hard Rubber Using a Hardness Tester". Samples were placed at 23±2℃ for 24 hours, and an Shore A hardness tester was used to apply pressure for 3 seconds before reading. At least 5 points were tested for each sample, and the average hardness and standard deviation were recorded. Units are dimensionless, n≥3, and the direction of the values ​​was determined according to the target scenario.

[0098] The dumbbell-shaped specimens from Examples 1–4 and all comparative examples were used as test objects to evaluate tensile strength and elongation at break, aiming to measure the influence of the continuous phase, filler dispersion, and flame retardant component loading on mechanical properties. The tests were conducted according to GB / T1040.2-2022 "Determination of tensile properties of plastics—Part 2: Test conditions for molded and extruded plastics". The specimens were placed at 23±2℃ for 24 hours, with a tensile speed of 500 mm / min. The maximum tensile force, fracture displacement, effective cross-sectional area, and gauge length changes were recorded. The average tensile strength, standard deviation of tensile strength, average elongation at break, and standard deviation of elongation at break were obtained, with n≥3.

[0099] Examples 1–4 and all comparative examples were used as test objects to evaluate the oxygen index, aiming to compare the effects of different formulations and variations in the proportions of magnesium hydroxide and ammonium polyphosphate on flame retardant performance. The tests were conducted according to GB / T2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics – Part 2: Room Temperature Test". Vertical strip specimens were used, and the samples were tested after being conditioned at 23±2℃. The oxygen concentration required to maintain combustion was recorded. The average oxygen index and standard deviation of the oxygen index were obtained, expressed as %, with n≥3. A higher value indicates a stronger flame retardant tendency.

[0100] Using the granules from Examples 1–4 and all comparative examples as test objects, the melt mass flow rate was evaluated to characterize the relationship between processing fluidity and plasticizing, lubrication, and filler dispersion. The tests were conducted according to GB / T3682.1-2018 "Plastics - Determination of melt mass flow rate and melt volumetric flow rate - Part 1: Standard method", with a set temperature of 190℃ and a load of 2.16 kg. Samples were treated under the corresponding drying conditions before testing, and the extrusion mass was recorded over 10 minutes. The average and standard deviation of the melt mass flow rate were obtained, in g / 10min, with n≥3.

[0101] Using the molded sheets from Examples 1–4 and all comparative examples as test subjects, the total volatile organic compound (TVOC) emissions were evaluated to confirm the contributions of non-phthalate plasticizers, vacuum degassing, and stabilizing components to low odor and low emissions. The tests were conducted in a 1 m³ environmental chamber at a temperature of 65 ± 2 °C, relative humidity of 50 ± 10%, and an air exchange rate of 1.0 ± 0.1 h. - ¹ After equilibration for 2.0 h, the outlet gas was collected using an adsorption tube and analyzed by gas chromatography. The sample size, sample mass, exposure area, chamber volume, sampling volume, background concentration of the environmental chamber, total volatile organic compound concentration, blank subtraction method, and number of repetitions were recorded. The average value and standard deviation of the total volatile organic compound release were obtained, in mg / m³, with n≥3.

[0102] The plasticizer migration rate was evaluated using the molded sheets from Examples 1–4 and all comparative examples. The molded sheets were used as samples, and all samples were tested with the same contact medium, contact time, and contact temperature. The sample contact conditions, contact area, contact medium, contact time, contact temperature, mass changes before and after the test, and sensory changes were recorded. The average value and standard deviation of the plasticizer migration rate were obtained, with n≥3.

[0103] Figure 1 This diagram illustrates the effect of maleic anhydride-grafted polypropylene (MPP) content on tensile strength and melt flow rate in the rubber-plastic composite material of this invention. Based on Example 1, only the MPP content was varied to investigate the effect of compatibilizer dosage within the range of 0.30–9.00 wt% on material properties. The results show that when the MPP content is too low, the interfacial bonding between the polar inorganic component and the non-polar polyolefin continuous phase is insufficient, resulting in limited improvement in tensile strength. When the content is too high, the viscoelastic behavior and melt flow state of the system are affected, which is detrimental to stable extrusion. A moderate content can achieve a balance between interfacial bonding and melt flow, indicating that the compatibilizer is an important factor in achieving both strength improvement and processing stability. Comprehensive performance analysis shows that when the MPP content is 0.50–8.00 wt%, the mechanical strength and processing fluidity can be maintained at the target levels of this invention.

[0104] Figure 2 This diagram illustrates the effect of the D50 particle size of surface-modified calcium carbonate on the tensile strength and elongation at break of the rubber-plastic composite material in this scheme. The filler addition amount, plasticizing system, and processing temperature were kept constant, with only the D50 particle size of the surface-modified calcium carbonate being varied. The results show that excessively small particle size tends to increase the specific surface area and melt viscosity of the system, leading to increased difficulty in filler dispersion; excessively large particle size easily forms localized stress concentration points, reducing elongation at break and interfacial load-bearing capacity. When the D50 particle size is at a moderate level, the filler can play a reinforcing role without significantly impairing the deformability of the elastic continuous phase, demonstrating that reasonable particle size control is beneficial for balancing material strength and toughness.

[0105] Figure 3 This diagram illustrates the effect of twin-screw extrusion processing temperature on tensile strength and melt flow rate of the rubber-plastic composite material in this scheme. Based on the formulation of Example 1, only the extrusion processing temperature was varied to examine the effect of a temperature window within the range of 120–220°C on material properties. The results show that at lower processing temperatures, the thermoplastic elastomer, polyolefin resin, and plasticizer are insufficiently plasticized, and the filler is difficult to fully wet and disperse. At higher processing temperatures, the system may experience localized thermal oxidation, plasticizer volatilization, or decreased interfacial structural stability. A suitable processing temperature can simultaneously ensure melt plasticization, filler dispersion, and extrusion stability, indicating the rationality of the processing window adopted in this scheme.

[0106] Figure 4 This diagram illustrates the effect of non-phthalate plasticizer content on tensile strength and melt flow rate of the rubber-plastic composite material in this scheme. The amounts of resin, filler, and compatibilizer are fixed, and only the non-phthalate plasticizer content is varied. The results show that increasing the plasticizer content improves melt flowability and reduces extrusion processing resistance; however, when the plasticizer content is too high, the cohesive strength of the continuous phase decreases, and the tensile strength of the material shows a downward trend. A moderate amount can maintain high mechanical strength while improving processing flowability, indicating that this scheme does not simply rely on plasticizers to improve flowability, but rather achieves simultaneous optimization of processing performance and mechanical properties through the synergistic regulation of plasticization, compatibilization, and filler dispersion.

[0107] Based on the determination of the key formulation and process parameters mentioned above, we further verified the source of performance improvement from the perspective of filler dispersion structure. Figure 5 The graph shows the differential distribution of filler agglomeration size in the rubber-plastic composite material of this scheme, characterizing the filler agglomeration size in Example 1 and related comparative samples. The results show that the agglomeration size distribution peak of Example 1 is more concentrated and shifts to the smaller size region, indicating that the surface-modified calcium carbonate can enter the continuous phase of rubber and plastic more uniformly under the action of the compatibility system, reducing the formation of coarse agglomerates and thus reducing the risk of local stress concentration. Figure 6 This is a cumulative distribution curve of filler agglomeration size in the rubber-plastic composite material of this scheme. The difference in agglomeration size between Example 1 and the control sample is further compared through cumulative distribution. The results show that the agglomeration size corresponding to Example 1 is smaller at the same cumulative percentage, indicating that its D50 and high quantile agglomeration size are effectively controlled, further proving that the combined effect of surface-treated filler and compatibilizer can improve the dispersion state of the highly filled system.

[0108] Figure 7This diagram illustrates the relationship between melt flow rate and tensile strength of the rubber-plastic composite material in this scheme. A comprehensive comparison of the processing fluidity and mechanical strength of Example 1 and related comparative samples is presented. The results show that Example 1 maintains a good melt flow rate while still exhibiting high tensile strength, without displaying the phenomenon of "increased fluidity but significant decrease in strength" common in conventional high-plasticity systems. This indicates that this scheme alleviates the contradiction between processing fluidity and mechanical load-bearing capacity by improving interfacial bonding through maleic anhydride-grafted polypropylene, reducing filler agglomeration through surface-modified calcium carbonate, and regulating melt flow through non-phthalate plasticizers.

[0109] To further verify the material's safety, flame retardancy, and thermal stability beyond its mechanical properties, Figure 8 This chart shows a comprehensive comparison of the oxygen index and tensile strength of the rubber-plastic composite material presented in this solution. Example 1 and related flame-retardant samples were evaluated side-by-side. The results show that Example 1, while exhibiting a high oxygen index, still maintains good tensile strength, indicating that the halogen-free flame-retardant component and inorganic filler system did not significantly disrupt the continuous phase structure formed by the thermoplastic elastomer and polyolefin resin. Therefore, under the formulation and testing conditions corresponding to Example 1, this solution can improve flame retardancy while maintaining the material's mechanical properties, solving the problem of strength reduction or embrittlement after flame-retardant filling reinforcement in traditional environmentally friendly rubber-plastic materials.

[0110] Figure 9 The thermogravimetric analysis (TGA) mass retention curve of the rubber-plastic composite material of this scheme is shown, comparing the mass retention of Example 1 and related comparative samples during the heating process. The results show that Example 1 exhibits a higher mass retention rate and a higher residual rate in the main thermogravimetric range, indicating that the combined effect of surface-modified inorganic filler, halogen-free flame-retardant component, and stabilizing component can delay matrix degradation and improve the structural stability of char or inorganic residues under heating conditions. This result further demonstrates that this scheme not only improves the mechanical properties at room temperature but also enhances the material's structural retention ability under thermal conditions.

[0111] Figure 10This chart compares the total volatile organic compound (TVOC) emissions and plasticizer migration rates of the rubber-plastic composites presented in this scheme, evaluating the low-release and low-migration performance of Examples 1–4 and related comparative samples. The results show that Example 1 exhibits low TVOC emissions and plasticizer migration rates, indicating that the non-phthalate plasticizer used has good compatibility with the thermoplastic elastomer, polyolefin resin, and compatibility interface, reducing the tendency of the plasticizer component to migrate during subsequent use. This result demonstrates that this scheme improves melt flowability without sacrificing the material's low volatility and low migration performance, thus addressing the challenge of balancing processing flowability and environmental stability. The TVOC emissions and plasticizer migration rates among different formulation samples are jointly determined by the polymer matrix, plasticizer, natural rubber, filler, flame retardant components, and processing exhaust conditions. Figure 10 The data in the sample were used to evaluate the overall release and migration performance of the corresponding formulation samples.

[0112] To ensure the stability of the above performance results based on the raw materials, further quality control verification was conducted on the auxiliary plasticizers and stabilizing components. Figure 11 This is a scatter plot showing the quality control of epoxy values ​​for epoxidized soybean oil in this scheme, comparing the epoxy values ​​of epoxidized soybean oil used in different embodiments. The results show that the epoxy values ​​of each sample are within a stable range, and the epoxy value level corresponding to Example 1 is moderate, indicating that epoxidized soybean oil can provide stable auxiliary plasticizing and processing stabilization effects. Figure 12 This is a scatter plot showing the acid value quality control of epoxidized soybean oil in this scheme, comparing the acid values ​​of epoxidized soybean oil used in different embodiments. The results show that the overall acid value of each sample is low, indicating that there are fewer free acidic components in the raw materials, which is beneficial to reducing side reactions and interfacial instability factors during processing. Figure 13 This is a scatter plot showing the volatile matter content of the epoxidized soybean oil in this scheme, comparing the volatile matter levels of the epoxidized soybean oil used in different embodiments. The results show that maintaining the volatile matter content within a low range helps reduce processing odor, decrease the risk of subsequent release, and provides raw material-level support for the low TVOC performance of the material. These results demonstrate that this scheme not only has a synergistic effect in terms of formulation ratios but also provides a stable foundation in the quality control of key raw materials.

[0113] In terms of macroscopic forming effect, Figure 14 The images show macroscopic optical photographs comparing the low-volatile rubber and plastic material granules and extruded sheets of Example 1 with the final product of Comparative Example 2, demonstrating the effect of surface-modified calcium carbonate and the compatibility processing system on the appearance continuity and molding stability of highly filled rubber and plastic materials. Figure 14a is a macroscopic optical photograph of the final product of Example 1. The sample includes low-volatile rubber and plastic material granules and extruded sheets, wherein the surface-modified calcium carbonate content is 30.00 wt%, the D50 particle size is 10.00 μm, and the stearic acid surface treatment amount is 2.50 wt%. Under the conditions of 35.00 wt% inorganic filler and 5.00 wt% halogen-free flame retardant component, the surface of the sheet remains continuous and uniform, and no coke particles, bubbles, or white powder exposure are observed, indicating that Example 1 has good melt mixing stability and extrusion molding adaptability. Figure 14 b is a macroscopic optical photograph of the final product of Comparative Example 2, in which unmodified calcium carbonate was used instead of surface-modified calcium carbonate, and the rest of the main formulation and processing conditions were kept the same as in Example 1. As can be seen from the comparison, the unmodified filler is more likely to cause a decrease in the uniformity of the sheet surface, powder exposure, or local molding defects, indicating that the surface-modified filler system has a direct effect on improving the macroscopic integrity of highly filled rubber and plastic materials.

[0114] In terms of micromorphology, Figure 15 The images show a comparison of the scanning electron microscope morphology of the low-volatile rubber and plastic product granules and extruded sheets of Example 1 with the final product of Comparative Example 2, used to demonstrate the role of surface-modified calcium carbonate in filler dispersion, interfacial bonding, and surface defect control in highly filled rubber and plastic composite systems. Figure 15 a is a low-magnification scanning electron microscope image of the final product of Example 1, showing a large-scale continuous morphology of the sheet surface or frozen section, with no macropores, coarse agglomerates or white areas of powder observed; Figure 15 b is a low-magnification scanning electron microscope image of the final product of Comparative Example 2, used to compare the filler enrichment, local roughness, and large-scale non-uniform regions in the unmodified calcium carbonate system. Figure 15 c is a scanning electron microscope image of the final product of Example 1, showing that the surface-modified calcium carbonate with a D50 particle size of 10.00 μm and other inorganic components are relatively uniformly distributed in the polymer matrix; Figure 15 Image d is a high-resolution scanning electron microscope image of the final product of Comparative Example 2, used to compare the aggregation tendency of unmodified calcium carbonate in the rubber-plastic matrix. Figure 15 e is a high-magnification scanning electron microscope image of the final product of Example 1, showing that the edges of the filler particles are well covered by the polymer matrix and the filler / matrix interface is tightly bonded. Figure 15 f is a high-magnification scanning electron microscope image of the final product of Comparative Example 2. It can be seen that interfacial voids, micropores, or particle pull-out marks are more likely to appear around the unmodified filler. The above SEM results are consistent with... Figures 5 to 7 The correlation between agglomeration size and performance results corroborate each other, indicating that the surface-modified filler and compatibility processing system in Example 1 can support the improvement of material strength, toughness and processing stability at the microstructure level.

[0115] Further verification was conducted from the perspective of local structure and element distribution. Figure 16 The images show a transmission electron microscope comparison of the low-volatile rubber and plastic product granules and extruded sheets of Example 1 with the final product of Comparative Example 2, used to demonstrate the local distribution, interfacial coating, and crystal structure retention of inorganic fillers in the polymer matrix in Example 1. Figure 16 a is a bright-field transmission electron microscope image of the final product of Example 1, showing that the inorganic components such as surface-modified calcium carbonate, talc, magnesium hydroxide and ammonium polyphosphate can form a relatively stable local dispersion state in the polymer matrix; Figure 16 b is a bright-field transmission electron microscope image of the final product of Comparative Example 2, used to compare the local aggregation of fillers, low-density voids at the interface, or discontinuous coating phenomena in the unmodified calcium carbonate system. Figure 16 c is a high-resolution transmission electron microscope image of the final product of Example 1, showing local lattice fringes of the inorganic filler, indicating that the melt processing process did not destroy the structural characteristics of the main inorganic crystal components such as calcium carbonate, magnesium hydroxide or talc. Figure 16 d is a high-resolution transmission electron microscope image of the final product of Comparative Example 2, used to compare the structural state of the local crystal edges and interface regions of the unmodified filler. Figure 16 e is the elemental distribution diagram of the final product of Example 1, showing that elements such as Ca, Mg, P, and O are relatively uniformly distributed in local areas, proving that the reinforcing filler and halogen-free flame retardant components can be well co-dispersed in the rubber and plastic matrix; Figure 16 f is the elemental distribution diagram of the final product of Comparative Example 2, used to compare the elemental enrichment and uneven local distribution caused by unmodified calcium carbonate. It can be seen that Example 1, through the combination of filler surface treatment, compatibilizer interface control, and melt blending processes, achieves a synergistic relationship between filler reinforcement, halogen-free flame retardancy, processing flowability, and low migration stability. From both structural and performance perspectives, this demonstrates that the proposed solution can effectively address the problem of balancing the comprehensive performance of environmentally friendly rubber and plastic materials.

[0116] Table 1 Performance of Examples and Comparative Examples

[0117] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 achieve a differentiated balance among hardness, tensile strength, elongation at break, oxygen index, processing fluidity, and low release indicators. The conventional comparative examples, due to plasticizer replacement, changes in filler surface condition, particle size deviation, absence of compatible modifiers, or changes in process conditions, show localized decreases in mechanical, flow, or release indicators. In the synergistic comparative examples 9–11, the oxygen index and mechanical retention trends were not as good as in Example 1 when either magnesium hydroxide or ammonium polyphosphate was retained individually or its ratio was deviated. This indicates that under the formulation system and test conditions corresponding to Example 1, magnesium hydroxide and ammonium polyphosphate, when combined in the stated ratio, can demonstrate a synergistic relationship between flame retardancy and mechanical retention.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A low-volatile rubber and plastic product material, characterized in that, Based on a total mass of 100 wt% of the low-volatile rubber and plastic product material formulation, it consists of the following formulation components, and the sum of the contents of each formulation component is 100 wt%: Thermoplastic elastomers 30.00-65.00 wt%; The polyolefin resin comprises 10.00-35.00 wt%, wherein the polyolefin resin includes one or two of polypropylene or polyethylene and maleic anhydride-grafted polypropylene, wherein the content of maleic anhydride-grafted polypropylene is 0.50-8.00 wt% and is included in the content of the polyolefin resin. Natural rubber 0.00-25.00wt%; The inorganic filler comprises 5.00-35.00 wt%, wherein the inorganic filler includes surface-modified calcium carbonate, and the content of the surface-modified calcium carbonate is 5.00-30.00 wt% and is included in the content of the inorganic filler; Non-phthalate plasticizers 5.00-30.00 wt%; Halogen-free flame retardant component 0.00-25.00wt%; Stable components: 0.10-3.00 wt%; Lubricating processing components: 0.10-3.00 wt%; Phthalate plasticizers, halogenated flame retardants, and lead salt stabilizers are not added as ingredients in the formulation of the low-volatile rubber and plastic products.

2. The low-volatile rubber and plastic product material according to claim 1, characterized in that, The respective components in the formulation composition satisfy the following limitations: The thermoplastic elastomer is selected from one or both of styrene-ethylene / butene-styrene block copolymers or styrene-ethylene / propylene-styrene block copolymers. The matrix polyolefin resin in the polyolefin resin is selected from one or both of polypropylene and polyethylene. The inorganic filler is surface-modified calcium carbonate, or is composed of surface-modified calcium carbonate and talc. The non-phthalate plasticizer is selected from one or two of acetylated tributyl citrate and epoxidized soybean oil; The halogen-free flame retardant component with a content greater than 0 is selected from one or more of magnesium hydroxide, aluminum hydroxide, ammonium polyphosphate, or melamine cyanurate; The stabilizing component comprises calcium stearate, zinc stearate, and one or two selected from pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite; The lubricating component is selected from one or more of stearic acid, polyethylene wax, or erucamide.

3. The low-volatile rubber and plastic product material according to claim 2, characterized in that, The thermoplastic elastomer is a styrene-ethylene / butene-styrene block copolymer, and the quality control parameters of the styrene-ethylene / butene-styrene block copolymer are: styrene content of 15.00-35.00 wt%, number average molecular weight of 50,000-250,000 g / mol, and butadiene segment hydrogenation degree of 95.00-99.90%. The styrene content and the butadiene segment hydrogenation degree are determined by proton nuclear magnetic resonance spectroscopy with deuterated chloroform as solvent, and the number average molecular weight is determined by gel permeation chromatography with tetrahydrofuran as mobile phase and polystyrene as calibration standard.

4. The low-volatile rubber and plastic product material according to claim 2, characterized in that, The non-phthalate plasticizer includes epoxidized soybean oil, and the content of the epoxidized soybean oil is included in the content of the non-phthalate plasticizer. The quality control parameters of the epoxidized soybean oil are: epoxy value of 5.50-7.50%, acid value not higher than 1.00 mg KOH / g, and volatile matter not higher than 0.50 wt%. The epoxy value is determined by hydrochloric acid-acetone method or hydrobromic acid-glacial acetic acid method, the acid value is determined by potassium hydroxide titration method, and the volatile matter is determined by heating loss method.

5. The low-volatile rubber and plastic product material according to claim 2, characterized in that, The halogen-free flame retardant component and the stabilizing component satisfy the following conditions: The content of the halogen-free flame retardant component is greater than 0, and the halogen-free flame retardant component is composed of magnesium hydroxide and ammonium polyphosphate, and the mass ratio of magnesium hydroxide to ammonium polyphosphate is 1:0.20-2.

00. The stabilizing component consists of calcium stearate, zinc stearate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite, in a mass ratio of 1:0.20-2.00:0.05-1.00:0.05-1.

00.

6. A method for preparing a low-volatile rubber and plastic product material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Weigh the formulation components according to the formulation amount of any one of claims 1-5, and premix the thermoplastic elastomer, the polyolefin resin, the natural rubber with a content greater than 0 in the formulation, the non-phthalate plasticizer, the stabilizing component and the lubricating processing component to obtain a first premix; S2. Add the inorganic filler and the halogen-free flame retardant component with a content greater than 0 in the formulation to the first premix, and continue mixing to obtain the second premix; S3. The second premix is ​​added to a twin-screw extruder for melt blending. The barrel temperature zone of the twin-screw extruder is set to 130-210℃, the screw speed is 100-600rpm, and the material residence time is 1.0-8.0min. S4. Extrude, cool, and pelletize the molten blend to obtain low-volatile rubber and plastic product granules; S5. The low-volatile rubber and plastic product material granules are extruded, injection molded, calendered or compression molded to obtain low-volatile rubber and plastic products.

7. The preparation method according to claim 6, characterized in that, In step S1, the premixing temperature is 20-60℃ and the premixing time is 3.0-20.0 min; in step S2, after the inorganic filler is added, the mixing temperature is 40-100℃ and the mixing time is 5.0-30.0 min.

8. The preparation method according to claim 6, characterized in that, In step S3, the twin-screw extruder is provided with multiple temperature zones along the material conveying direction, and the temperatures of the multiple temperature zones are 130-160℃, 150-180℃, 160-195℃ and 170-210℃ respectively; vacuum degassing is performed during the melt blending process, and the absolute pressure of the vacuum degassing section is 0.001-0.020MPa.

9. The preparation method according to claim 6, characterized in that, In step S4, the cooling is water cooling or air cooling, and the moisture content of the low-volatile rubber and plastic product material granules after cooling is 0.02-0.50 wt%; in step S5, the low-volatile rubber and plastic product material granules are dried at 60-90℃ for 1.0-6.0 h before molding, and the extrusion molding temperature is 140-210℃, the injection molding temperature is 150-220℃, and the compression molding temperature is 130-190℃.

10. The application of a low-volatile rubber and plastic product material according to any one of claims 1-5, characterized in that, The low-volatile rubber and plastic material is used to prepare daily necessities, household goods, sporting goods, wire and cable sheaths, sealing strips, floor mats, yoga mats, shoe materials, automotive interior parts, home floor mats, sports mats, or low-odor automotive interior mats. When the low-volatile rubber and plastic material contains the halogen-free flame-retardant component, it is used to prepare wire and cable sheaths; when the low-volatile rubber and plastic material does not contain the halogen-free flame-retardant component, it is used to prepare low-odor elastic cushioning sheets.

Citation Information

Patent Citations

  • Halogen-free flame-retardant thermoplastic elastomer material for wires and cables and preparation method of material

    CN105907019A